2021
DOI: 10.3390/plants10061034
|View full text |Cite
|
Sign up to set email alerts
|

Bioacaricidal Potential of Moringa oleifera Ethanol Extract for Tetranychus merganser Boudreaux (Acari: Tetranychidae) Control

Abstract: The Tetranychidae family includes mites causing severe damage to agricultural fields. The red spider mite, Tetranychus merganser Boudreaux (Acari: Tetranychidae), causes severe damage to several plant species grown as cash crops. Current red spider mite control depends mainly on chemical insecticides. There is a need for alternate control measures that are environmentally friendlier than chemical pesticides. The aim of the study was to assess the effects of Moringa oleifera leaf ethanolic extract at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The inhibition percentage was calculated according to the following equation: % Inhibition = ((Abs control − Abs sample)/(Abs control)) × 100 where Abs control is the absorbance of control without extract, and Abs sample is the absorbance of samples containing extracts. The IC 50 as the concentration of extracts leads to 50% inhibition, and IC 90 as the concentration leads to 90% inhibition of microorganism growth were estimated using SAS statistical software [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition percentage was calculated according to the following equation: % Inhibition = ((Abs control − Abs sample)/(Abs control)) × 100 where Abs control is the absorbance of control without extract, and Abs sample is the absorbance of samples containing extracts. The IC 50 as the concentration of extracts leads to 50% inhibition, and IC 90 as the concentration leads to 90% inhibition of microorganism growth were estimated using SAS statistical software [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other preventive control methods for T. merganser have been reported. They cause a minimal environmental impact, including predator mites ( Neoseiulius californicus McGregor and Amblyseius swirskii Athias-Henriot (Gamasida: Phytoseiidae)) [ 8 ], botanical extract ( Moringa oleifera ethanol extract) [ 11 ], and entomopathogenic fungi ( Metarhizium anisopliae s.l. and Beauveria bassiana ) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the red spider mites' short life cycle and high reproductive potential allows them to quickly develop resistance to these compounds [12]. The use of botanical extracts [13] and predatory mites, mainly from the family Phytoseiidae [4], are more effective and sustainable strategies to the management of red spider mites, with the added benefit of causing minimal impact on the environment. In Mexico, Chacón-Hernández et al [11] observed that wild chili pepper (C. annuum var.…”
Section: Introductionmentioning
confidence: 99%